2018
DOI: 10.1039/c8ce01441h
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Gd2O3:Eu3+/Tb3+ phosphors: preparation, luminescence properties and growth mechanism

Abstract: Columnar Gd2O3:Eu3+/Tb3+ phosphors were successfully prepared by a solvothermal method and subsequent calcination process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…According to the results in Figures and , the concentration quenching of Eu 3+ is 5% for Gd 2 O 2 S:Eu 3+ nanocrystals. In comparison, the quenching concentration of Gd 2 O 3 :Eu 3+ is 4% . The reasons for this quenching effect may include the following.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…According to the results in Figures and , the concentration quenching of Eu 3+ is 5% for Gd 2 O 2 S:Eu 3+ nanocrystals. In comparison, the quenching concentration of Gd 2 O 3 :Eu 3+ is 4% . The reasons for this quenching effect may include the following.…”
Section: Resultsmentioning
confidence: 96%
“…By comparing the emission spectrum of Gd 2 O 3 :Eu 3+ (as shown in literature 35 ) and Gd 2 O 2 S:Eu 3+ , it can be found that there are several differences. First, the optimum excitation wavelength (329 nm) of Gd 2 O 2 S:Eu 3+ is larger than that (250 nm) of Gd 2 O 3 :Eu 3+ .…”
Section: Luminescence Analysismentioning
confidence: 90%
See 1 more Smart Citation
“…Hence, both GO and PGO-Gd are presumed to contain an abundance of oxygenated surface functional groups, and that PGO-Gd, some of oxygen-containing groups replaced with Gd 2 O 3 nanoparticles. At 1200 • C, weight loss for GO was ~67%, and PGO-Gd was observed 26%, which was related to the formation of cubic Gd 2 O 3 by the phase transition from hexagonal Gd(OH) 3 of PGO-Gd [38]. These results suggest a higher stability and surface functionality of PGO-Gd than that of GO.…”
Section: Pgo-gd Structural Chracterizationmentioning
confidence: 90%
“…12-0797). This indicates the successful integration of Gd 2 O 3 into PGO [38]. The TGA approach was used to measure the amount of oxygenated functionals on the surface of GO and PGO-Gd by oxidative decomposition from 25 • C to 1200 • C at a rate of 10 • C min −1 , as illustrated in Figure S1.…”
Section: Pgo-gd Structural Chracterizationmentioning
confidence: 99%